2019
DOI: 10.3892/etm.2019.7738
|View full text |Cite
|
Sign up to set email alerts
|

miR‑448 promotes progression of non‑small‑cell lung cancer via targeting SIRT1

Abstract: Deregulation of microRNAs (miRs) has been demonstrated to be involved in both the initiation and the development of non-small-cell lung cancer (NSCLC). miR-448 has been identified as a tumor suppressor in several cancer types. The aim of the present study was to explore the role of miR-448 in NSCLC. Tumor tissues and paired normal tissues were obtained from patients with NSCLC. The viability and migration of A549 cells were determined by the Cell Counting kit-8 and wound-healing assays, respectively. Gene and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The specific primers were as follows: TMPO-AS1: 5’-AGCCAGACCTCTACAATCGG-3’ (forward) and 5’-TTAGGATTCTTGCGGGTGGT-3’ (reverse); hsa-miR-143-3p: 5’-TGAGATGAAGCACTGTAGCTC-3’ (forward) and 5’-GAGCTACAGTGCTTCATCTCA-3’ (reverse); CDK1: 5’-TGGGGTCAGCTCGTTACTCA-3’ (forward) and 5’-CACTTCTGGCCACACTTCATTTA-3’ (reverse); U6: 5’-CTCGCTTCGGCAGCACA-3’ (forward) and 5’-AACGCTTCACGAATTTGCGT-3’ (reverse), GAPDH: 5’-CCTGCACCACCAACTGCTTA-3’ (forward) and 5’-GGCCATCCACAGTCTTCTGAG-3’ (reverse), 23 among which GAPDH and U6 were performed as internal reference control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific primers were as follows: TMPO-AS1: 5’-AGCCAGACCTCTACAATCGG-3’ (forward) and 5’-TTAGGATTCTTGCGGGTGGT-3’ (reverse); hsa-miR-143-3p: 5’-TGAGATGAAGCACTGTAGCTC-3’ (forward) and 5’-GAGCTACAGTGCTTCATCTCA-3’ (reverse); CDK1: 5’-TGGGGTCAGCTCGTTACTCA-3’ (forward) and 5’-CACTTCTGGCCACACTTCATTTA-3’ (reverse); U6: 5’-CTCGCTTCGGCAGCACA-3’ (forward) and 5’-AACGCTTCACGAATTTGCGT-3’ (reverse), GAPDH: 5’-CCTGCACCACCAACTGCTTA-3’ (forward) and 5’-GGCCATCCACAGTCTTCTGAG-3’ (reverse), 23 among which GAPDH and U6 were performed as internal reference control.…”
Section: Methodsmentioning
confidence: 99%
“…Then qRT-PCR was operated with BlazeTaq™ SYBR Green qRT-PCR Mix (BioCat, Heidelberg, Germany) in PCR machine CFX96 Touch (Bio-Rad, California, US) under following conditions: 2 minutes at 95 C, 45 cycles for 5 seconds at 94 C and 40 seconds at 60 C. Then the comparative cycle threshold (CT) method (2 ÀDDCT) was used to calculate the relative expression of each mRNA. 22 The specific primers were as follows: TMPO-AS1: 5'-AGC CAGACCTCTACAATCGG-3' (forward) and 5'-TTAG GATTCTTGCGGGTGGT-3' (reverse); hsa-miR-143-3p: 5'-TGAGATGAAGCACTGTAGCTC-3' (forward) and 5'-GAGCTACAGTGCTTCATCTCA-3' (reverse); CDK1: 5'-TGGGGTCAGCTCGTTACTCA-3' (forward) and 5'-CA CTTCTGGCCACACTTCATTTA-3' (reverse); U6: 5'-CTCG CTTCGGCAGCACA-3' (forward) and 5'-AACGCTTCACG AATTTGCGT-3' (reverse), GAPDH: 5'-CCTGCACCACC AACTGCTTA-3' (forward) and 5'-GGCCATCCACAGTC TTCTGAG-3' (reverse), 23 among which GAPDH and U6 were performed as internal reference control.…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%
“…Qi et al confirmed that SIRT1 is the direct target of miR-448 through double luciferase reporter gene detection. Activation of SIRT1 would reverse the EMT growth inhibition ability of non-small cell lung cancer cells induced by miR-448 mimetics and play a destructive role (29). The above results showed that after lentivirus infected sh-SIRT1 interferes with SIRT1 and down-regulates expression, the expression level of adhesion molecules which aggregate among cells such as α-catenin, PTEN, and Ecadherin was up-regulated, and finally the proliferation and EMT of breast cancer cells were inhibited.…”
Section: Discussionmentioning
confidence: 86%
“…In particular, Conditional Sirt1 deletion in the hematopoietic stem and progenitor system promotes hematopoietic stem and progenitor cell (HSPC) expansion under stress conditions [23]. Moreover, SIRT1 enhances progression and epithelial-mesenchymal transition in several cancer [24,25]. Furthermore, CyclinD1 promotes the cancer cell growth dependent on autophagy [26].…”
Section: Introductionmentioning
confidence: 99%